Respuesta :
Answer:
-65.5
Step-by-step explanation:
(5/3)*x+(1/3)*x = (8/3)*x+131/3 // - (8/3)*x+131/3
(5/3)*x+(1/3)*x-((8/3)*x)-(131/3) = 0
(5/3)*x+(1/3)*x+(-8/3)*x-131/3 = 0
-2/3*x-131/3 = 0 // + 131/3
-2/3*x = 131/3 // : -2/3
x = 131/3/(-2/3)
x = -131/2
x = -131/2
The calculation to the given expression can be defined as follows:
Given:
[tex]\bold{\frac{5}{3} x + \frac{1}{3}x = 13 \frac{1}{3} + \frac{8}{3}x}[/tex]
To find:
x=?
Solution:
[tex]\to \bold{\frac{5}{3} x + \frac{1}{3}x = 13 \frac{1}{3} + \frac{8}{3}x}\\\\\to \bold{\frac{5}{3} x + \frac{1}{3}x - \frac{8}{3}x= 13 \frac{1}{3}}\\\\\to \bold{ x(\frac{5}{3} + \frac{1}{3} - \frac{8}{3})= 13 \frac{1}{3}}\\\\\to \bold{ x(\frac{5+1-8}{3} )= 13 \frac{1}{3}}\\\\\to \bold{ x(\frac{-2}{3} )= \frac{40}{3}}\\\\\to \bold{ x = - \frac{40}{3} \times \frac{3}{2}}\\\\\to \bold{ x = - 20}\\\\[/tex]
Therefore, the final answer of x is "-20".
Learn more:
brainly.com/question/13729904